An Empirical Analysis of Behavioral Finance in the Saudi Stock Market: Evidence of Overconfidence Behavior - Alsabban, Soleman; Alarfaj, Omar (International Journal of Economics and Financial Issues, 2019)
Theoretically, investors are considered to be rational decision makers in regards to trading in stock markets, however, some empirical studies have statistically discredited this believe. Evidence shows that investors seem to act irrationally in the financial markets. This research, therefore, aims to empirically investigate investor’s irrational behavior, specifically, overconfidence behavior in the Saudi stock market, Tadawul. The data under investigation is from 2007 to 2018, monthly based. According to previous research, positive past market returns influence the level of investors’ overconfidence leading to higher trading turnover in stock markets. To test for overconfidence behavior, a market-wide Vector autoregression (VAR) model is designed to investigate the lead-lag relationship between market returns and market turnover. The results obtained in this research suggest that investors in the Saudi stock market are overconfident. Keywords: Behavioral Finance, overconfidence bias, stock market, VAR JEL Classifications: D91, G11, G12, G15, E22, G4 DOI: https://doi.org/10.32479/ijefi.8920